Neurologic sequelae of phosphide poisoning: A case report - Shafiee Dolat Abadi, Sahel; Zamani, Nasim; Abbasi, Sahar; Shojaei, Maziar; Hassanian-Moghaddam, Hossein (Frontiers in Neurology, 2022)
Background: Aluminum phosphide (ALP) is extremely toxic with a high mortality rate, mainly due to its cardiovascular complications. Some neurologic effects have also been reported with this pesticide. Case presentation: We present a 23-year-old male who presented with confusion after ingestion of a toxic dose of ALP. Computerized tomography scan demonstrated diffuse bilateral hypoattenuation of the cerebellar hemispheres, midbrain, thalamus, and globus pallidus resulting in tonsillar and transtentorial herniation and eventually brain death four days after admission. Conclusions: This is the first documented case of neurologic sequela following phosphide poisoning that emphasizes the importance of brain imaging studies for patients with loss of consciousness.